Evaluation of radiation induced bystander effect (RIBE) involving MCF-7 and hFOB 1.19 cells following bismuth oxides nanoparticles treatment in radiotherapy - Zainudin, Nur Hamizah Mohd (2021)
In radiotherapy, nanoparticles have been widely investigated as potential radiosensitizer to increase the radiation lethal effects on cancer cells. Targeted nanoparticles to the cancer cells might reduce the unnecessary radiation dose to healthy tissues. Nevertheless, the presence of nanoparticles might also trigger the responses of non-targeted cells to radiation or the radiation-induced bystander effect (RIBE). In this research, evaluation on the RIBE due to bismuth oxide nanoparticles (Bi2O3 NPs) application during radiotherapy in human breast cancer MCF-7 and normal osteoblast hFOB 1.19 cells were conducted. The studies were performed using external beam radiotherapy of photon and electron beams as well as high dose-rate (HDR) brachytherapy. RIBE stimulation was performed through a medium transfer technique. Reactive oxygen species (ROS), cell viability, cell survival, apoptosis assays and Fourier Transform Infrared (FTIR) spectroscopy were employed to evaluate the effect. The results demonstrated that MCF-7 and hFOB 1.19 bystander cells were able to maintain their proliferation for more than 80% after 48 hours incubation with irradiated-cell conditioned medium (ICCM) treated with Bi2O3 NPs. The bystander cells also present a positive response in their ability to sustain the survival up to 80% after treatment with ICCM for 10 days. The ROS level increased in the bystander cells, but the addition of Bi2O3 NPs did not significantly increase the ROS level. Observation on the apoptosis level in MCF-7 and hFOB 1.19 cells concerning the radiation dose or addition of Bi2O3 NPs compared to control group also present no significant increase. The absorbance levels at wavenumber 1080 cm-1 (symmetric PO2– stretching of the DNA) were almost identical for treated and untreated group of both cells. The amplitude of the peaks located at 1040 cm-1 corresponding to the symmetric PO2– stretching in DNA and RNA indicate changes approximately around 10%. In conclusion, the finding in this study provides evidence that the use of Bi2O3 NPs as radiosensitizer in radiotherapy does not significantly increase the RIBE responses in non-targeted cells.